The effect of planting density on water use efficiency, growth and yield of four chickpea (Cicer arietinum L.) genotypes having contrasting growth patterns - Leboho, Terry Moraka (My University, 2020)
Field experiments were conducted at two locations; University of Limpopo (Syferkuil) and University of Venda (Thohoyandou) during 2015 and 2016 winter cropping seasons. The objectives of this study were to determine; the effect of genotype (ACC# 1, 3, 4 and 7) and planting density (33, 25 and 20 plants/m2) on four chickpea genotypes having contrasting growth patterns and also to determine the effect genotype and planting density on water use and water use efficiency of four chickpea genotypes having contrasting growth patterns. The experimental design was randomized complete block design in factorial arrangement with three replications. Plant height, number of primary and secondary branches, grain yield and yield components (number of pods per plant, number of seeds per pod, Harvest Index and 100 seed weight [100-SW] and above ground biomass, and were determined at different growth stages. Data obtained was subjected to analyses of variance using the general linear model of Genstat 17th edition. Significant differences between the treatments means were compared using the standard error of difference (LSD) of the means at 5% level. Correlation analyses were performed to assess the relationship between parameters. Plant height varied with genotype from 41 cm (84 DAE) to 44 cm (118 cm) at Syferkuil and 41 (56 DAE) to 44 cm (63 DAE) at Thohoyandou. Primary branches was not significantly affected by genotype and planting density at both locations and seasons. Planting density had significant effect on number of secondary branches, greater number was recorded at low (32, 6) density at Syferkuil in 2016. Above ground biomass was significantly affected by planting density at Syferkuil during in 2015 (5344 kg ha-1) and 2016 (3701 kg ha-1) growing seasons. Genotype and planting density did not affect number of pods plant-1, number of seeds plant-1, 100 SW (100 seed weight), and Harvest index were not significant at both locations and seasons. Grain yield was significantly affected by planting density at Syferkuil in 2015 and Thohoyandou in 2016. Grain yield increased with the increase in planting density at both locations. Two field experiments were conducted at University of Venda (Thohoyandou) during 2015 and 2016 winter cropping seasons. This study aimed at assessing the effect of genotype v and planting density on water use efficiency of four chickpea genotypes with contrasting growth patterns. Crop water use (WU) was determined by monitoring soil water content at 7-day intervals using a neutron probe and, water use efficiency (WUE) was determined as a ratio of crop biomass and grain yield to WU. Genotype and planting density had no significant effect on WU in 2015 and 2016. Genotype and planting density had no significant effect on biomass production (WUEb) and grain yield production (WUEg) in 2015. In contrast, WUEb and WUEg was significantly affected by planting density in 2016. WUEb was 43.2% greater at high density compared to low density. Similarly, WUEg was 39.3% greater at high density compared to low density. WUEb and WUEg increased with the increase with planting density. Therefore, manipulation of management practices such as planting density may increase chickpea production. Keywords: Planting density, genotype, grain yield and yield components, water use efficiency.
Thesis (M. A. (Agricultural Management)) -- University of Limpopo, 2020
Keywords: Planting density; Genotype; Grain yield; Yield components; Water use efficiency.; Corn - Planting; Chickpea; Genotype-environment interaction